Determining Acceptable Planting Dates for Growing Pumpkin - Toramatov R. G.; Shokirov A. J.; Abdurashidov I. D. (Web of Journals Publishing, 2023)
In the spring, pumpkin seeds of the Shirintoy and Palov varieties were planted in a field (280+70)/2×70 cm in 4 periods, April 1-10-20 and April 30, and the effect on yield was studied. In the variant planted on April 10, the Shirintoy variety was 20.9-28.0% higher than the other variants, and in the variant planted on April 1-2, the Palav pumpkin variety was 14.3-37.2% higher than the following options.